Bacterioplankton communities reveal horizontal and vertical influence of an Island Mass Effect. (12th June 2022) - Comstock, Jacqueline; Nelson, Craig E.; James, Anna; Wear, Emma; Baetge, Nicholas; Remple, Kristina; Juknavorian, Amethyst; Carlson, Craig A.
Summary: Coral reefs are highly productive ecosystems with distinct biogeochemistry and biology nestled within unproductive oligotrophic gyres. Coral reef islands have often been associated with a nearshore enhancement in phytoplankton, a phenomenon known as the Island Mass Effect (IME). Despite being documented more than 60 years ago, much remains unknown about the extent and drivers of IMEs. Here we utilized 16S rRNA gene metabarcoding as a biological tracer to elucidate horizontal and vertical influence of an IME around the islands of Mo′orea and Tahiti, French Polynesia. We show that those nearshore oceanic stations with elevated chlorophyll a included bacterioplankton found in high abundance in the reef environment, suggesting advection of reef water is the source of altered nearshore biogeochemistry. We also observed communities in the nearshore deep chlorophyll maximum (DCM) with enhanced abundances of upper euphotic bacterioplankton that correlated with intrusions of low‐density, O2 rich water, suggesting island influence extends into the DCM.